Single-step immobilization of hydroxyapatite on fluoropolymer surfaces for enhanced cell adhesion; Materials Letters; Vol. 363 - Goreninsky (Goreninskii) S. I. Semen Igorevich; Akimchenko I. O. Igor Olegovich; Vorobjev A. O. Aleksandr Olegovich; Nashchekin A. V. Alexey Viktorovich; Nashchekina Yu. Yulia; Bolbasov E. N. Evgeny Nikolaevich (2024, 2024)
Title screen